Six-minute walk distance and survival time in patients with idiopathic pulmonary fibrosis in Brazil - Mancuzo, Eliane Viana (J Bras Pneumol, 2018)
OBJECTIVE: To determine the cut-off point for the six-minute walk distance (6MWD) that indicates lower survival time in patients with idiopathic pulmonary fibrosis (IPF) in Brazil. METHODS: This was retrospective study carried out in two referral centers for IPF. The 6MWT was performed twice, considering the highest value of the 6MWD. Various cut-off points were estimated, in absolute values and in percentage of predicted values, using ROC curves, the Kaplan-Meier method, and data from other studies. RESULTS: The sample comprised 70 patients with IPF. The mean age was 71.9 ± 6.4 years, and 50 patients (71.4%) were male. The mean FVC was 76.6 ± 18.2% of predicted value. The mean SpO(2) at rest before and after 6MWT were 93.8 ± 2.5% and 85.3 ± 6.5%, respectively. The median survival time was 44 months (95% CI: 37-51 months). The mean 6MWD was 381 ± 115 m (79.2 ± 24.0% of predicted). After the analyses, the best cut-off points for estimating survival were 6MWD < 330 m and < 70% of predicted. The median survival time of patients with a 6MWD < 330 m was 24 months (95% CI: 3-45 months), whereas that of those with a 6MWD ≥ 330 m was 59 months (95% CI: 41-77 months; p = 0.009). Similarly, the median survival times of those with a 6MWD < 70% and ≥ 70% of predicted, respectively, were 24 months (95% CI: 13-35 months) and 59 months (95% CI: 38-80 months; p = 0.013). Cox multivariate regression models including age, sex, smoking status, SpO(2) at the end of the 6MWT, and FVC% showed that 6MWD remained significantly associated with survival (p = 0.003). CONCLUSIONS: Values of 6MWD < 330 m and < 70% of predicted value were associated with lower survival time in IPF patients in Brazil.